Layers of learning in coach developers` practice-theories, preparation and delivery - Stodter, A.; Cushion, C. J. (International Sport Coaching Journal, 2019)
Despite the centrality of coach developers to formal coach education settings, only a handful of studies have begun to touch upon the role they play in mediating quality learning, while links between different layers of learning and impact on coach learners remains underexplored. This research explored English coach developers` understanding of learning, and the learning frameworks taught to them, through unstructured interviews and participant observation of a generic coach developer training course. Three coach developers were observed delivering formal coach education, to elucidate how understanding was applied in practice. Supporting interviews with 16 coaches attending the course gave an indication of reactions to developers` practice. Combined layers of data were analysed using a three-phase integrated analytic process. In the absence of pertinent evidence-informed coach developer training course design and delivery, implicit `practice-theories`, based on participants` experiences as coaches and coach developers, appeared to inform understanding and practices. Despite acknowledging `learner centred` learning principles, coach developers experienced challenges implementing these in practice and coach learners perceived confusion and contradictions. Findings are discussed in relation to contemporary ideas around coaches` and coach developers` learning, to highlight potential ways that coach developers could be more effectively prepared and supported.